Initial Experience in a Pig Model of Robotic-Assisted Intracranial Arteriovenous Malformation (AVM) Embolization. Issue 2 (20th December 2019) - Desai, Virendra R; Lee, Jonathan J; Tomas, Johnny; Lumsden, Alan; Britz, Gavin W
Abstract: BACKGROUND: Robotic assistance for coronary and peripheral vascular pathologies is steadily gaining popularity. However, it has yet to be applied to neurovascular intervention. OBJECTIVE: To establish the feasibility of the CorPath ® GRX robotic-assisted platform (Corindus Inc, Waltham, Massachusetts) for intracranial arteriovenous malformation (AVM) embolization. METHODS: This robotic system was used to embolize intracranial AVMs (n = 4) in 2 anesthetized pigs, under controlled conditions appropriate for clinical intervention. Initially, a catheter was manually introduced into the common carotid artery (CCA). Then, the robotic system was used to advance the catheter into the ascending pharyngeal artery (APA) towards the rete mirabilis, which was used as a model for an AVM, using 0.014 in guidewires and 2.4F/1.7F microcatheters. After doing a pre-embolization APA run, which demonstrated good visualization of the rete, dimethyl sulfoxide (DMSO) was instilled into the microcatheter. A negative roadmap was then done, and Onyx was used to embolize the rete. RESULTS: All 4 AVMs were completely obliterated with no complications, including no contrast extravasation, dissection, thrombosis, or other vascular injury. CONCLUSION: This study is the first to demonstrate the feasibility of a robotic-assisted platform for intracranial AVM embolization.